2007
DOI: 10.1152/ajpgi.00187.2007
|View full text |Cite
|
Sign up to set email alerts
|

A role of Wnt/β-catenin signals in hepatic fate specification of human umbilical cord blood-derived mesenchymal stem cells

Abstract: Human umbilical cord blood-derived mesenchymal stem cells (UCBMSCs) are expected to be an excellent source of cells for transplantation. In addition, the stem cell plasticity of human UCBMSCs, which can transdifferentiate into hepatocytes, has been reported. However, the mechanisms involved remain to be clarified. To identify the genes and/or signals that are important in specifying the hepatic fate of human UCBMSCs, we analyzed gene expression profiles during the hepatic differentiation of UCBMSCs with human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
63
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 49 publications
2
63
1
Order By: Relevance
“…34 Our results are consistent with other studies suggesting that down-regulation of Wnt/b-catenin signaling is necessary for stem cell differentiation. 10,11 The presence of Wnt ligands can enhance the binding of b-catenin to androgen receptor (AR) and promote AR-mediated transcription. 35 Others suggested that IL-6 might modulate the AR nuclear transactivation via STAT3, MAPK, or other signaling cascades.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Our results are consistent with other studies suggesting that down-regulation of Wnt/b-catenin signaling is necessary for stem cell differentiation. 10,11 The presence of Wnt ligands can enhance the binding of b-catenin to androgen receptor (AR) and promote AR-mediated transcription. 35 Others suggested that IL-6 might modulate the AR nuclear transactivation via STAT3, MAPK, or other signaling cascades.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that suppression of the Wnt/b-catenin signaling pathway promotes hepatic differentiation of MSCs derived from bone marrow or umbilical cord blood. 10,11 In embryonic development, Wnt-5a represents the major suppression modulator of Wnt/b-catenin signaling. Overexpression of Wnt-5a promotes GSK-3b-independent b-catenin degradation, suggesting an oncosuppression effect.…”
mentioning
confidence: 99%
“…Therefore, many studies have examined the mechanisms underlying the differentiation ability of MSCs. Several recent studies (Yoshida et al, 2007;Ishii et al, 2008;Liu et al, 2015) have demonstrated that Wnt/β-catenin signaling plays an important role in regulating the hepatic differentiation of human MSCs. Upon Wnt signaling activation, β-catenin will translocate into the nucleus and coactivate downstream transcription factors to regulate the differentiation of MSCs.…”
Section: Fig 2 Signaling Pathway Of Liver Fibrogenisismentioning
confidence: 99%
“…During the hepatoblast formation by both hepatic liver cells and biliary epithelial cells [ 14 ], Wnt/β-catenin is known to promote cell proliferation and differentiation along with the formation of progenitor hepatocytes [ 101 ]. The activation of this signalling pathway allows the conversion of non-hepatic endodermal cells to a hepatoblast condition.…”
Section: Livermentioning
confidence: 99%